Semantic Priming in Dutch Children: Word Meaning Integration and Study Modality Effects. Issue 3 (28th March 2017) - van der Ven, Frauke; Takashima, Atsuko; Segers, Eliane; Verhoeven, Ludo
Abstract : Research in adults has shown that novel words are encoded rather swiftly but that their semantic integration occurs more slowly and that studying definitions presented in a written modality may benefit integration. It is unclear, however, how semantic integration proceeds in children, who (compared to adults) have more malleable brains and less reading knowledge. In this study, 68 Dutch‐speaking children studied novel words, together with their meanings presented orally or in writing. After 22 hours, children showed semantic priming effects for novel words, demonstrating semantic integration, but the amount of priming did not differ between the two study modalities. Thus, children appeared to integrate newly learned word meanings independently of the modality in which they studied the definitions. This implies that semantic integration in 10‐ to 13‐year‐olds can occur, as with adults, within 24 hours, but may be unaffected by the modality in which the meanings are studied.